PENYETARAAN TES UAN: MENGAPA DAN BAGAIMANA? - SukimoDS SukimoDS (Jurnal Cakrawala Pendidikan, 2007)
Debates concerningwhat is right and what is wrOng with national finalexamination (UAN) in Indonesiaare not new. National Final Examination (UAN),a significant processusing a test form to measure learning output, has beendeveloped to provide useful information for the decision makers (parents,educators,policy"makers and the local community). Multiple forms of acertificationexam are desirable for a variety of reasons. However, the problem ofcomparabilityamong test scores using different test forms must be addressed inorder to insure fairness and consistency in each testing situation. Test forms mustbe interchangeable across test administrations. Psychometric procedures known asequatingmethods can be utiliz~d to produce comparable (equated) scores.Equating procedures consist of(1) a design for collecting test data for equating, (2)a clearly defined level of expected correspondence among test scores, and (3)specific statistical procedures that areused to estimate score correspondence. Theprocess ofequating is used to obtain comparable scores when more than .one testforms areused in a test administration. In many situations in test administration,morethan one form of the tests are used for security reasons. Beside, by testequating, a test form can be administered more flexible in the context ofenvironmentand time. There are several techniques and methodologies that can he usedin equating test fonns. Generally speaking, these techniques and methodologies can hedivided into three major activities, namely determining test equating desigu, determiningthe test equating methods, and determining the wayof test equating will be taken. Themagnitude of standard error of estimate (SEE) is used to evaluate which is the mostaccuratemethod of test equating. The less the score of standard error of estimatethe more accurateof the test equating method